Molecular evolution under low recombination - Kaiser, Vera B. (The University of Edinburgh, 2009)
Analyzing regions in the genome with low levels of recombination helps understand the prevalence of sexual reproduction. Here, I show that variability in regions of reduced recombination in Drosophila can be explained by interference among strongly deleterious mutations; selection becomes progressively less effective in influencing the behaviour of neighbouring sites as the number of closely linked sites on a chromosome increases. I also show that the accumulation of loss-of-function mutations on the neo-Y chromosome of Drosophila miranda is compatible with a model of selection against such mutations alone, without the need to invoke the action of selective sweeps. I describe the discovery of two new sex-linked genes in the plant Silene latifolia, SlCyt and SlX9/SlY9. SlCyt has been recently translocated from an autosome to the X and shows signs of a selective sweep. Its possible role in having caused recombination arrest between the evolving X and Y chromosome is discussed. SlX9 still has an intact Y-linked copy that is presumably functional. Nucleotide diversity at SlY9 is very low, whereas SlX9 has an unusually high diversity and shows signs of introgression from S. dioica into S. latifolia, but the effect of this seems very localized.
Keywords: genomic engineering; recombination; mutation; neo-Y chromosome